2020
DOI: 10.1186/s13068-020-01788-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the effects of morphological changes on extracellular electron transfer rates in cyanobacteria

Abstract: Background: Understanding the extracellular electron transport pathways in cyanobacteria is a major factor towards developing biophotovoltaics. Stressing cyanobacteria cells environmentally and then probing changes in physiology or metabolism following a significant change in electron transfer rates is a common approach for investigating the electron path from cell to electrode. However, such studies have not explored how the cells' concurrent morphological adaptations to the applied stresses affect electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Fe (-)|20% CO 2 cells, were found to be elongated by up to 1.6 µm relative to Fe (-)|Air cells (Fig. S5) and by ≈0.5-0.8 µm relative to cells grown in standard conditions (reported in previous work) 16 . In S. elongatus, this phenotype indicates elevated levels of RpaA-P, which implies a reduction/interruption in normal CikA activity 19,22 .…”
Section: Three Modes Are Identified As Candidate Circadian Rhythmssupporting
confidence: 65%
See 2 more Smart Citations
“…Fe (-)|20% CO 2 cells, were found to be elongated by up to 1.6 µm relative to Fe (-)|Air cells (Fig. S5) and by ≈0.5-0.8 µm relative to cells grown in standard conditions (reported in previous work) 16 . In S. elongatus, this phenotype indicates elevated levels of RpaA-P, which implies a reduction/interruption in normal CikA activity 19,22 .…”
Section: Three Modes Are Identified As Candidate Circadian Rhythmssupporting
confidence: 65%
“…This is particularly true for the Fe (+)|Air condition, where redox active ferric ions are assimilated by the cells. We previously estimated that the concentration of ferric ions in fresh BG11 medium reduces by half within four days of culturing and reduces to almost zero within 11 days under similar growth conditions 16 . Similar rates of ferric ion depletion rates in S. elongatus cultures have been independently reported from atomic absorption spectroscopy concentration measurements 17 .…”
Section: Current Density Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is the different shapes of the cells, as Synechocystis and Synechococcus are spherical and rod-shaped, respectively, and cell morphology has been predicted to have a role in exoelectrogenesis. 42 But the exact reason for the difference in their photocurrent profiles remains to be determined and will be the subject of future studies examining other model organisms. 43 We observed that spheroplasts, without an integrous periplasmic space, 37 yielded a monophasic photocurrent profile distinct from the complex profile of whole cells.…”
Section: Discussionmentioning
confidence: 99%
“…A stock culture of the cyanobacterium Synechococcus elongatus sp. PCC7942 (Pasteur Culture Collection), PCC7942 henceforth, was grown in liquid Blue-green medium (BG11) and cell concentration (cells ml −1 ) determined as previously described in previous work 23 . BPV devices were constructed as a galvanic electrochemical cell with a membrane electrode assembly (MEA).…”
Section: Cyanobacteria Culturing Conditionsmentioning
confidence: 99%